Local currency bond markets, foreign investor participation, and capital flow volatility in emerging Asia - John Beirne; Nuobu Renzhi; Ulrich Volz (Asian Development Bank Institute (ADBI), 2021)
This paper examines the role of local currency bond markets (LCBMs) and foreign investor participation in these markets in capital flow volatility in emerging Asian economies over the period 1999 to 2020. Using a panel analysis and impulse response functions generated from a panel structural vector autoregression, we show that greater development of LCBMs across ten Asian emerging economies in terms of capitalization helps to mitigate against capital flow volatility, while foreign investor participation has the opposite effect, particularly for less developed LCBMs. Our findings have policy implications from a financial stability perspective, whereby continued efforts to enhance LCBMs while reducing reliance on foreign investors should be encouraged. Strengthening the local investor base and mobilizing domestic resources through LCBMs ought to be a priority for raising long-term capital that will enable the financing of sustainable investment and development. Our findings also suggest that greater efforts are needed to enhance foreign exchange hedging arrangements for foreign investors in LCBMs, particularly in times of heightened financial stress.
Keywords: F32; F41; F62; 330; capital flow volatility; local currency bond markets